Electromigration-induced formation of percolating adsorbate islands during condensation from the gaseous phase: a computational study - Dvornichenko, Alina V.; Kharchenko, Vasyl O.; Kharchenko, Dmitrii O. (Beilstein Journal of Nanotechnology, 2021)
We provide a computational study of a change in the morphology of a growing thin film during condensation caused by electromigration effects. It will be shown, that separated circular adsorbate islands, realized in an isotropic system, become elongated in the direction of the applied electrical field. We discuss the dependence of the critical value of the strength of the applied electrical field, responsible for the formation of percolating adsorbate islands, on main control parameters. This study provides insight into details of electromigration effects during the self-organization of adatoms into percolating adsorbate islands during condensation from the gaseous phase. We will show that the elongated morphology of adsorbate islands remains stable if the electric field is turned off.
Keywords: adsorptive systems; electromigration; numerical simulations; pattern formation; thin films